2013
DOI: 10.1186/1471-2164-14-137
|View full text |Cite
|
Sign up to set email alerts
|

A SNP resource for Douglas-fir: de novo transcriptome assembly and SNP detection and validation

Abstract: BackgroundDouglas-fir (Pseudotsuga menziesii), one of the most economically and ecologically important tree species in the world, also has one of the largest tree breeding programs. Although the coastal and interior varieties of Douglas-fir (vars. menziesii and glauca) are native to North America, the coastal variety is also widely planted for timber production in Europe, New Zealand, Australia, and Chile. Our main goal was to develop a SNP resource large enough to facilitate genomic selection in Douglas-fir b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 74 publications
1
77
0
Order By: Relevance
“…Genome-wide SNP-based dendrogram analysis definitely provided an efficient and accuracy tool to address the genetic relationship of the germplasms and it will help us to select more divergent parents to improve the diversity of the seed orchard, as well as to better protect and manage them in the future. For conifer SNP genotyping, whole genome sequencing remained unattainable, but flexible methods such as population RNA-seq, EST re-sequencing approach and specific SNP array seemed to be rather feasible (Uchiyama et al, 2012;Howe et al, 2013;Liu et al, 2014;Plomion et al, 2014;Heer et al, 2016). In this study, we demonstrated that SLAF-seq is also an efficient method for the population SNP genotyping in conifer (Chinese fir).…”
Section: Resultsmentioning
confidence: 87%
“…Genome-wide SNP-based dendrogram analysis definitely provided an efficient and accuracy tool to address the genetic relationship of the germplasms and it will help us to select more divergent parents to improve the diversity of the seed orchard, as well as to better protect and manage them in the future. For conifer SNP genotyping, whole genome sequencing remained unattainable, but flexible methods such as population RNA-seq, EST re-sequencing approach and specific SNP array seemed to be rather feasible (Uchiyama et al, 2012;Howe et al, 2013;Liu et al, 2014;Plomion et al, 2014;Heer et al, 2016). In this study, we demonstrated that SLAF-seq is also an efficient method for the population SNP genotyping in conifer (Chinese fir).…”
Section: Resultsmentioning
confidence: 87%
“…Sequencing of cDNAs, genomes, and transcriptomes accelerated the discovery of SNPs and the development of large SNP databases for several conifers (Howe et al, 2013;Pavy et al, 2013a;Canales et al, 2014;Pinosio et al, 2014). The landscape of nucleotide diversity showed that the frequency of nucleotide polymorphisms varied significantly across gene families as a function of genes that appear to be specific to conifers and the breadth of expression patterns (Pavy et al, 2013a).…”
Section: Snp Discoverymentioning
confidence: 99%
“…The landscape of nucleotide diversity showed that the frequency of nucleotide polymorphisms varied significantly across gene families as a function of genes that appear to be specific to conifers and the breadth of expression patterns (Pavy et al, 2013a). SNPs have been used to design high-throughput genotyping chips of broad coverage in species of spruce and pine as well as Douglas fir (Pseudotsuga menziesii) and other conifer species (Chancerel et al, 2011(Chancerel et al, , 2013Pavy et al, 2012Pavy et al, , 2013bHowe et al, 2013). They have been used to conduct various structural and population genome scans for genetic linkage mapping (see below) and for large-scale association studies with phenotypic and environmental variation in spruces, pines, and Douglas fir (Eckert et al, 2012;Prunier et al, 2013;De La Torre et al, 2014b).…”
Section: Snp Discoverymentioning
confidence: 99%
“…Due to the dominance of Douglas-fir across a wide array of environments and heterogeneous landscapes in western Oregon (Hermann and Lavender, 1990; Ohmann and Spies, 1998) and its characteristic high levels of phenotypic and genetic variability (St. Clair et al, 2005; Eckert et al, 2009; Krutovsky et al, 2009; Howe et al, 2013), a relationship between geography and molecular composition and abundance is possible, regardless of whether genetics or environmental conditions are responsible for wood chemical variation.…”
mentioning
confidence: 99%